Development of a Negotiation Support Model for Value Management in Construction - Utomo, Christiono (2010)
Decision making for value-based design in Value Management (VM) is very complicated due to the involvement of many parties. In such situation where the designer, project manager, facility manager and others are involved in choosing a single alternative from a set of solutions, a negotiation support is required to evaluate and rank the solution before engaging into negotiation. This research presents a conceptual model of negotiation support for VM. It consists of developing the appropriate research approach, methodology of negotiation and agent-based negotiation in VM. The research objectives are to find a theoretical basis and research approach for negotiation support methodology on VM, to develop a decision model for technical solution options in a satisfying function/cost preferences, to investigate negotiation style and outcome and analyze the correlation between them for the basis of scenarios on the agent system, to develop a model for agreement options and coalition algorithms on value-based decision, to validate the coalition algorithms and introduce an initial model of Negotiation Support for Value Management (NSVM). A triangulation methodology has been used to fulfill the objectives. It combines simultaneous triangulation by using case studies and survey methods and sequential triangulation in which results of one method are essential in planning the next method (theoretical mapping, survey research, focus group, case study and conceptual modeling). The methodology is based on a theoretical approach which consists of value-based decision nature in construction VM, multicriteria group decision making, game theory, negotiation theory, and agent-based development. This methodology combines value analysis method using Function Analysis System Technique (FAST); Life Cycle Cost analysis, group decision analysis method based on Analytical Hierarchy Process (AHP), and Game theory-based agent system to develop a negotiation support.